Carcinoma in situ of the cervix. Study of 51 cases - Campos Rey de Castro, Jorge (2015)
It has been studied 51 cases of cancer in situ of the cervix, discovered in a period of 4 years, during which 16,000 patients of both sexes were examined; 1,597 of them had the diagnostic of infiltrating cancer of the cervix which gives an incidence of 3.2 per cent for cancer in situ. The average age of the patients with cáncer in situ was 41.0 years, while that of infiltrating was 47 years. It is discussed the histologic criterion which permits the diagnostic of cancer in situ: differential diagnosis is made with the histologic changes provoked by pregnancy by trichomonas and with atypical metaplasia. We have found a larger proportion of cases in the endocervical canal with or without glandular involvement. Special emphasis is given to the importance of Papanicolaou's test to discover cancer in situ and in the convenience of the ring cervical biopsy in order to demonstrate if cancer is infiltrating or not. The cytodiagnosis test was positive in 82.2 per cent and in 8.9 per cent showed atypical cells. The evolution and prognosis of cancer in situ is discussed. Most of the cases were treated through histerectomy, which deprives us to establish conclusions with regard to the evolution of cancer in situ not treated, but reference is made to 51 case which since 1944 is without treatment and in which persists up to now, histological changes of cancer in situ.